Perancangan Gedung MICE KAI Corporate University Dengan Konsep Pendekatan Arsitektur Bioklimatik - Aguesti, Prosia (Universitas Mercu Buana, 2025)
Abstrak – Education and training center (PUSDIKLAT) Ir. H. Juanda, which is located in the city of Bandung, West Java, is currently focusing on developing the design of the MICE (Meeting, Incentives, Conferences, and Exhibitions) building and Front Plaza. The MICE building that will be designed will be able to accommodate various activities within it, including Office, Auditorium, Meeting Room, Gallery, Library, and Tennant Space / Retail. This is designed to meet the needs of HR activities during education. In development planning, this development has a land area of 27,669 M². The concept used in planning the design of this MICE building uses a Bioclimatic Architecture approach. Bioclimatic architecture according to (Krisdianto, Abadi, & Ekomadyo, 2011, p.23) is a synergistic approach to architectural design regarding climate, which integrates human psychology, climatology and integration of building physics in regional architecture. In essence, Bioclimatic architecture is a building created as a result of a response to the surrounding environment to create the expected thermal comfort that can be enjoyed by the human resources in the building for their activities.